The Obligations of Children toward Parents According to Law No.1 of 1974 - Indriani, Sekar; Ja'far, Hasbullah (Universitas Islam Sultan Agung, 2023)
This research aims to determine the obligations of children to parents in Jama’ah Forum Kopi Hikam in Sei Musam Village, Kec. Batang Serangan, Kab. Langkat based on Law No.1 of 1974; the application of obligations to parents in Jama’ah Forum Kopi Hikam. This research is empirical juridical research, using a legal sociology approach. Primary data sources were obtained by interviewing the Jama’ah Forum Kopi Hikam. The results showed that the Jama’ah Forum Kopi Hikam have not shown their obligations towards parents and some people also still do not fully carry out their obligations towards parents due to the absence of underlying knowledge. They think that just maintaining it shows that the service to parents has been carried out. However, this has not been fully fulfilled, and it is emphasized in Islamic law that the degree or position of parents takes precedence, and also the obligation to care for parents must still be carried out. In the view of Law No. 1 of 1974, children are obliged to respect their parents, obey their wishes and be responsible for all the needs of their parents, even if the parents are well-off. Because every child until he becomes an adult or is married, is still obliged to respect, obey and be responsible for the needs of parents. In other words, the obligations between children and parents are reciprocal, namely both parents are obliged to maintain and educate their children as well as possible until the child is married or can stand on his own and while a child is obliged to respect parents and obey their good wishes. When a child is considered an adult, they have obligations according to their abilities towards their parents and family.